Does retrenchment strategy mitigate earnings management? Evidence from Public Listed Companies in Malaysia - Ung, Likjing; Brahmana, Rayenda Khresna; Puah, Chin Hong (Munich University Library, 2014)
During the past three decades, many firms in developing market have embarked retrenchment strategy in order to defend firm going concern from economy turbulence. Yet, this strategy is rarely investigated compared to another strategy like diversi fication. This is not to mention limited research investigating whether companies might manipulate their earnings through the retrenchment costs across ownership expropriation . As Malaysia offers unique background earnings management, corporate strategy and ownership structure, t his study aims to answer intriguing yet interesting question: Do Malaysia’s listed companies consider retrenchment costs when they manipulate earning across its ownership expropriation? Using 237 Malaysia n listed companies over th e period 2008 - 2013 , this study f oun d that retrenchment costs are used to manipulate earnings in companies. In addition, we find that ownership concentration do not significantly affects the earnings management of the firms.